Report from the Field: INTEGRATION AND EXPERIENCE IN THE SECONDARY CURRICULUM - Horwood, Bert (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1994)
A naturalistic study of an integrated curriculum package in a secondary school shows that, from the students’ perspectives, integration does not happen because the subjects are combined together. Rather, analysis of the students’ statements, combined with other sources of information such as parent interviews, participant observation, and the teacher’s plan book, reveals four integrating factors which transcend the disciplines. The four factors which students experienced are complete process, authenticity, community, and responsibility. The critical presence of such factors leads to explication of two different ways of understanding curriculum integration. One way is to think ofintegration as combining the subjects together in close proximity of time and space. The other way is to think of integration as arising from general factors, such as those identified, which cut across all subjects. RÉSUMÉ Une étude naturaliste des programmes d’études intégrés dans une école secondaire révèle que selon les étudiants, l’intégration n’a pas lieu en raison du simple fait que les sujets sont regroupés ensemble. En revanche, l’analyse des déclarations des étudiants combinée à d’autres sources d’information comme des entrevues avec les parents, l’observation des participants et le livre de plan des enseignants révèle quatre facteurs d’intégration qui transcendent les disciplines. Ces quatre facteurs sont selon les étudiants le processus complet, l’authenticité, la communauté et la responsabilité. La présence cruciale de ces facteurs explique deux façons différentes de comprendre l’intégration des programmes d’études. L’une consiste à voir dans l’intégration la combinaison des sujets dans une étroite proximité de temps et d’espace. L’autre consiste à voir dans l’intégration le résultat de facteurs généraux comme ceux qui sont précisés et que l’on retrouve dans tous les sujets.